ANALISIS PENGALAMAN BERMAIN GIM MOBILE LEGENDS DALAM MODE RANKED DAN NON RANKED (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2025)
Advances in digital technology have driven rapid growth in the interactive entertainment industry, including mobile-based video games. One popular game in Southeast Asia, particularly Indonesia, is Mobile Legends: Bang Bang (MLBB). In the four years since its release, Mobile Legends has achieved immense popularity, particularly in Southeast Asia, and has become one of the most sought-after games in the region. This game offers various game modes, including ranked (competitive) and non-ranked modes such as classic, each with distinct characteristics. The differences in the characteristics of these two modes likely have the potential to influence players' subjective perceptions and experiences during gameplay. The player experience encompasses various psychological dimensions such as enjoyment, emotional engagement, sense of accomplishment, and perceived levels of pressure or stress. Therefore, it is important to examine how each mode impacts players' gaming experiences. This study aims to analyze the differences in gaming experiences across these two modes using the Game Experience Questionnaire (GEQ), which encompasses seven main variables: competence, immersion, flow, tension, challenge, and positive and negative affect. The approach used was quantitative, with a quasi-experimental design involving 73 active MLBB players. This research is expected to contribute to academic understanding of the dynamics of gaming experiences in competitive and casual contexts, as well as provide input for developing game designs that are more adaptive to user preferences.